(untitled) (Balneo and PRM Research Journal, 2024)
Nanobiotechnology, an emerging stream, is an amalgamation of nanotechnology and biology. It involves synthesis of metallic nanoparticles mediated by biological materials of both plant and animal origins. The biological process of synthesis of nanoparticles is ecofriendly, requires less labor, and has many unique properties, derived from the biological matter used in their synthesis. The synthesis of metallic nanoparticles has to be followed by the characterization for different properties such as size, shape, capping materials, stability etc, which helps in clearly defining the synthesized nanoparticles on the basis of the observied properties. Keeping our past works, synthesis and characterization of nanoparticles in the background, we have reviewed different techniques utilized for characterization of metallic nanoparticles synthesized using biological agents. This review will serve as a comprehensive guide, assisting in better understanding techniques for characterization of metallic nanoparticles synthesized using biological agents. Keywords: nanotechnology; nanoparticles; UV-Vis, FT-IR, SEM, TEM, DLS, Zeta Potential, characterization